Preterm infant gut microbial patterns related to the development of necrotizing enterocolitis. (1st February 2020) - Lindberg, Tristan P.; Caimano, Melissa J.; Hagadorn, James I.; Bennett, Erin M.; Maas, Kendra; Brownell, Elizabeth A.; Matson, Adam P.
Abstract: Objectives: To define gut microbial patterns in preterm infants with and without necrotizing enterocolitis (NEC) and to characterize clinical factors related to the composition of the preterm intestinal microbiome. Methods: Fecal samples were collected at one-week intervals from infants with gestational ages <30 weeks at a single level IV neonatal intensive care unit. Using 16S rRNA gene sequencing, the composition and diversity of microbiota were determined in samples collected from five NEC infants and five matched controls. Hierarchical linear regression was used to identify clinical factors related to microbial diversity and specific bacterial signatures. Results: Low levels of diversity were demonstrated in samples obtained from all preterm infants and antibiotic exposure further decreased diversity among both NEC cases and controls. Fecal microbial composition differed between NEC cases and controls, with a greater abundance of Proteobacteria and bacteria belonging to the class Gammaproteobacteria among NEC infants. Control infants demonstrated a greater abundance of bacteria belonging to the phylum Firmicutes . Conclusion: These findings indicate that an association exists between intestinal Proteobacteria and NEC, and strengthens the notion that an overly exuberant response to Gram-negative products, particularly lipopolysaccharide, in the preterm intestine is involved in NEC pathogenesis. Cumulative exposure to antibiotics corresponded to a reduction in microbial diversity in both NEC cases and controls.